"Pondok" system as a model for retirement village in Malaysia: a legal perspective - Sufian, Azlinor; Mohamad, Nor Asiah (University Putra Malaysia, 2013)
The Traditional Islamic Educational Institution (hereinafter referred to as “Pondok”) has been established as part of formal traditional religious educational system in Malaysia. There are many literatures on Pondok (among others by Ismail Ishak, 1990, Azmi Omar, 1993 and Hasan Md Man, 1990) which focussed on syllabus that are taught in Pondok and methodology of teachings that are engaged in Pondok. Albeit none of the available literatures discuss the issues related to the operation of Pondok from a legal perspective whereby it is quite crucial to determine the relationship between the operator (management of the Pondok institution) and occupier (who can be a tenant/lessee/licensee/unit owner/student- depending on the nature of modus operandi of the Pondok). Clear determination of the rights and obligations of these two stakeholders will enhance the protection of interest and welfare of the affected parties as there would be several legal implications that may derived from the establishment of this relationship. The Pondok is generally well received by many Malay Muslims either for young adults or aged peoples. Nevertheless the current trend shows that, apart from being a place for seeking education, Pondok has been developed to be a place for aged people to seek continual religious education as well as a new settlement that suits their needs within a sociable and supportive environment. The aim of this paper is to look into the legal set up of the Pondok, rights and duties of the Pondok Operator and the occupiers, legal status of the occupiers and management of the common properties within the Pondok. This research will involve the case study of two (2) Pondok that specifically cater the aged people in two different states in Malaysia and a comparative study with the retirement village law and concept practiced in New South Wales, Australia. The findings of the study reveal that there is a need to have a proper legal framework for the management of Pondok in Malaysia as it involves the management of physical, financial and legal matters related thereto.